EVALUASI MEKANISME PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 23 (Studi Kasus PT Batik Danar Hadi Solo) - Desi Putri Lestari, Fadjar Harimurti & Djoko Kristianto (Universitas Slamet Riyadi, 2017)
This research uses descriptive method with qualitative approach. The type andis used primary and secondary data. The data collection was done by interview, inthe PT Solo Batik Danar Hadi. In the income tax under Article 23 of the cuttingprocess, deposit and reporting where the company as the cutter has fulfilled the taxobligations by always trying to cut deposit and reporting on the use of such serviceseach month before the deadline for reporting that comes with proof of slaughter anddeliver letters notification (SPT) Period. Based on the research results, PTBatikDana Hadi has implemented cuts and income tax reporting Article 23 in accordancewith applicable tax regulations. In this study we can conclude PT Batik Danar Hadihas to perform his duty well in cutting, reporting income tax under Article 23 andpreferably in depositing Income Tax Article 23 carried out on time in accordancewith the provisions of tax laws deposit, which is the 10th of the following month andreporting, which is the 20th of the following month after tax period.Keywords: Cutting, remittance, reporting, article 23